2011
DOI: 10.2134/jeq2010.0443
|View full text |Cite
|
Sign up to set email alerts
|

Field Evaluation of a New Plastic Film (Vapor Safe) to Reduce Fumigant Emissions and Improve Distribution in Soil

Abstract: Preplant soil fumigation is an important pest management practice in coastal California strawberry production regions. Potential atmospheric emissions of fumigants from field treatment, however, have drawn intensive environmental and human health concerns; increasingly stringent regulations on fumigant use have spurred research on low-emission application techniques. The objectives of this research were to determine the effects of a new low-permeability film, commonly known as totally impermeable film (TIF), o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
44
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 23 publications
3
44
1
Order By: Relevance
“…2A). The flux values after tarp cutting (13 days after application) in the fall 2009 trial were substantially lower than those reported (over 200 µg m −2 s −1 ) when tarp cutting occurred 6 days after fumigant application (Qin et al 2011). Emissions of chloropicrin were lower than 1,3-D emissions (data not shown) because of the lower amount of chloropicrin applied and its faster degradation; following an application of Telone C35, it's 1,3-D that is the major concern for worker safety in an emissions surge.…”
contrasting
confidence: 70%
See 2 more Smart Citations
“…2A). The flux values after tarp cutting (13 days after application) in the fall 2009 trial were substantially lower than those reported (over 200 µg m −2 s −1 ) when tarp cutting occurred 6 days after fumigant application (Qin et al 2011). Emissions of chloropicrin were lower than 1,3-D emissions (data not shown) because of the lower amount of chloropicrin applied and its faster degradation; following an application of Telone C35, it's 1,3-D that is the major concern for worker safety in an emissions surge.…”
contrasting
confidence: 70%
“…Our research objective was to optimize the use of TIF to reduce emissions, improve efficacy and potentially reduce fumigant application rates. This research was also conducted to determine how to avoid the surge of emissions that had been observed when TIF was cut after 6 days, the cutting time that is commonly used for standard polyethylene film (Qin et al 2011). This paper includes our research data for fumigant concentration in the air under the tarps (above soil Data from three field trials conducted near Parlier, above, show that totally impermeable film (TIF) maintained higher fumigant concentrations under tarp and in the soil than polyethylene film.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Emission flux and cumulative loss estimated using dynamic flux chambers were reported in Qin et al 2011. Emission flux of chloropicrin and 1,3-D from Field 2 (TIF) was substantially lower than from Field 1 (polyethylene film) during tarp covering.…”
Section: Oxnard Trial Resultsmentioning
confidence: 99%
“…Tarping fields with low permeability film, such as virtually impermeable film (VIF) or totally impermeable film (TIF), has been effective in retaining fumigants in soil (Gao et al 2013). These films can improve the efficacy of reduced fumigant application rates because they retain higher fumigant concentration and extend the exposure time (concentration × time) under the film compared to standard polyethylene film (Fennimore and Ajwa 2011;Qin et al 2011).…”
mentioning
confidence: 99%